AGRICULTURAL SEED FINANCING: IMPLICATIONS FOR PRODUCTIVITY AND EXPORT EARNINGS FOR NIGERIA ECONOMY - ZUBERU; ILIYA; YUSUF; SALIHU (International Journal of Research -GRANTHAALAYAH, 2017)
Since the discovery of oil, there has been a drastic decline in agricultural exports as percentage of total exports declined from about 43% to slightly over 7% between 1970 and 1974, as a result of the oil price shocks of 1973 – 1974 which resulted in large receipts of foreign exchange earnings by Nigeria and the neglect of agriculture. There have been series of declines in agricultural export since the mid-1970s at an average annual decline rate of 17 percent and by 1996, agricultural export accounted for only 2 percent of total exports, hence, making Nigeria net importer of basic food stuff. With this continual decline, the agricultural sector no longer earns enough foreign exchange through exports. Hence, this study investigates implications of agricultural seed financing on increased productivity output and export earnings in Nigeria. The choice of research design employed in this study is the archival and documentary research strategy, associated with the deductive approach, which involved secondary data collection. The population comprised 16 years data on total annual financial expenditure on agricultural seed improvement, agricultural productivity output and export earnings from 2000 to 2015 (16 years). Secondary data on cumulative annual expenditure on seed financing (SIF), Agricultural productivity (AP) indicator and export earnings (EE) were employed. The findings revealed that, findings revealed that Seed improvement financing has a significant impact on increased Agricultural production output and that there is a significant relationship between Agricultural production output and increased export earnings in Nigeria. The study therefore recommended that, there is need for the government to increase funding for agricultural research and also access international grants, as this will help increase variety of high yield seeds and subsequently increase agricultural production output, which will increase agro related export earnings in Nigeria.